Silagem de coproduto de fecularia de mandioca e de vitivinicultura em diferentes proporções - Schneider , Cibele Regina (2018)
A study was carried out to evaluate the fermentation profile and the microbiological characteristics of silage from coproduct of starch from cassava and vitiviniculture in different proportions and times of storage. The evaluated treatments were the proportions (0%, 25%, 50%, 75% and 100%) of wine production in silage of manioc starch co-product. The silages were evaluated at the time of silage and at 1, 3, 7, 15, 30 and 60 days of storage. The silages with higher proportions of vitiviniculture co-product obtained higher contents of dry matter, ammoniacal nitrogen and buffer capacity. Acid-lactic bacteria presented adequate population for the fermentation of the silages. Enterobacteria and yeasts obtained low values in all silages and times. There was an increase in effluent and gas losses over the storage period. The increase in the proportions of the wine production co-product was efficient due to the increase of the dry matter and soluble carbohydrates contents and to reduce losses due to effluents and gases. All silages were of good quality for microbiological parameters, pH and temperature up to 60 days of storage. In another study, the microbiological parameters and the aerobic stability of these silages were evaluated. The treatments evaluated were the same as in the previous study, with evaluations at 0, 30, 60, 90 and 120 days of storage. As the proportions of the wine-growing co-product increased, the levels of ammoniacal nitrogen and dry matter recovery increased and effluent and gas losses were reduced. The presence of enterobacteria and yeasts were low and the lactic acid bacteria and Clostridium spp. reduced over time. Only the silage from wine production co-products remained stable over time. The microbiological parameters of the silages were satisfactory due to the reduction of the undesirable microorganisms. The viticulture co-product increases silage stability, up to 120 days of storage, and reduces effluent and gas losses. Another objective was to evaluate the chemical-bromatological composition, the in vitro digestibility and the fractionation of proteins and carbohydrates. The treatments and opening times of the silos were the same as in the previous study. The content of dry matter, organic matter, neutral detergent fiber, acid detergent fiber, crude protein, ethereal extract and lignin, increased in the highest proportions of wine production coproducts. The in vitro digestibility of dry matter, organic matter, crude protein and cell wall, non-fibrous carbohydrates, total carbohydrates and soluble carbohydrates were higher in manioc starch silage. The fraction A of the protein was higher for the silage with 50% of each co-product, the fractions B1 and C increased with time, the fraction B3 obtained higher content for the cassava starch and B2 for the co-product of grape. The A + B1 fraction of carbohydrates was higher for manioc starch, fraction B2 increased and fraction C decreased with time. The substitution of the manioc starch coproduct for wine - growing residue increased the concentration of nutrients, but reduced digestibility.